Prevalence of Thromboembolic Events among Hospitalized COVID-19 Patients in Baluchistan - Amir Hamza, Abdul Wahid, Abdul Bari, Mohammad Azam, (Pakistan Journal of Medical & Health Sciences, 2025)
Objective: To find the frequency and types of thromboembolic events in hospitalized COVID-19 patients in Baluchistan. Method: This cross-sectional study was conducted at Bolan Medical College Hospital, Quetta from 1st May 2020 to 30th April 2021. A total of 340 RT-PCR confirmed COVID-19 patients aged over 18 years were included. Patients who were already on anticoagulation, had a history of thromboembolic disease, or were discharged within 24 hours were typically excluded. Demographics, comorbidities, symptoms, laboratory findings, imaging, and treatment were recorded. Thromboembolic events confirmed via Doppler ultrasound, computed tomography, or magnetic resonance imaging were also recorded. Results: Two hundred and sixteen (63.5%) were males and 124 (36.5%) were females with mean age was 57.4±14.8 years. Severe disease were occurred in 126 (37.1%), critical in 84 (24.7%), and mild/moderate in 130 (38.2%) patients. Thromboembolic events occurred in 78 patients (22.9%), including deep vein thrombosis (11.2%), pulmonary embolism (7.1%), and ischemic stroke (4.7%). Events were more frequent in critical patients and linked to intensive care unit admission (p<0.01). Anticoagulation was initiated in 204 patients (60%); 115 (56.4%) received low-molecular-weight heparin and 91 (44.6%) unfractionated heparin. Conclusion: Thromboembolic events were common in COVID-19 patients in Baluchistan. They occurred more in severe cases. Early anticoagulation helped reduce their frequency and improved outcomes. Keywords: Anticoagulation, COVID-19, Deep vein thrombosis, Pulmonary embolism, Stroke, Thromboembolic events, Venous thromboembolism